What's what in Japan's financial system (Japan, 1990)
This book introduce the organization of financial institutions, fanance business, interest rates and finance, financial markets. The bank of Japan and monetary policy, international finance.
Keywords: Tài chính,Finance; Nhật Bản,Japan